2022
DOI: 10.3390/polym14081613
|View full text |Cite
|
Sign up to set email alerts
|

Expandable Graphite as a Multifunctional Flame-Retarding Additive for Highly Filled Thermal Conductive Polymer Formulations

Abstract: Expandable graphite (EG) and graphite (G) were assessed as multifunctional additives improving both flame retardancy and thermal conductivity in highly filled, thermal conductive polymeric materials based on polyamide 6 (PA6). Fire testing was conducted using modern UL-94, LOI and cone calorimeter test setups. It is demonstrated that thermal conductivity can significantly influence the time to ignition, although offering little fire resistance once ignited even in highly filled systems. Thus, for PA6 formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The following chapter focuses on differences in the fire behavior found for flame-retardant non- and β-RC PA6 formulations. All flame-retardant additives tested are commercially available and have been extensively studied in the literature (MC [ 46 , 47 , 78 ], EG [ 50 , 51 , 52 , 79 ], AlPi [ 74 , 75 ], and IFR [ 80 ]). Thus, where appropriate, literature for further information is presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following chapter focuses on differences in the fire behavior found for flame-retardant non- and β-RC PA6 formulations. All flame-retardant additives tested are commercially available and have been extensively studied in the literature (MC [ 46 , 47 , 78 ], EG [ 50 , 51 , 52 , 79 ], AlPi [ 74 , 75 ], and IFR [ 80 ]). Thus, where appropriate, literature for further information is presented.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of expandable graphite, a high thermal conductivity provides an improved heat distortion effect, which has a positive effect on LOI testing results. A corresponding study addressing this issue can be found in [ 79 ]. β-RC formulations containing EG showed a comparable LOI development.…”
Section: Resultsmentioning
confidence: 99%
“…EG has not only the flame-retardant effect but also has minimal smoke production and low toxicity [25][26][27]. In addition to its properties as a flame retardant, EG also has good thermal and electrical conductivity, high strength, and stiffness [28,29]. These properties make it a universal material that can be used in a wide range of applications, e.g., flame retardant, conductive additive, absorbent, covering product, graphene precursor, and graphite foils.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make it a universal material that can be used in a wide range of applications, e.g., flame retardant, conductive additive, absorbent, covering product, graphene precursor, and graphite foils. Therefore, EG can be used in various fields including fire protection of wood, and the flame-retardant property of the composite of wood and EG improved as the total heat release rate (HRR) decreased [17,18,29]. The Bochemit Antiflash, based on boric acid and 2-aminoethanol, acts mainly chemically; its usage is limited (due to ammonia gas).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 6 (PA6) is increasingly utilized in various industrial applications, such as aerospace, automotive, and electronics, due to its corrosion resistance, high specific strength, and good formability [2]. Unfortunately, the thermal conductivity of PA6 is only 0.3 W m −1 K −1 [3], which limits its application in thermal conductive electronic components. Preparing filled PA6-based composites is a beneficial approach to improving the thermal conductivity of PA6.…”
Section: Introductionmentioning
confidence: 99%